Characteristic temperature of a 2 µm InGaSb/AlGaAsSb mode-locked quantum well laser - Li, Xiang (2018)
Mode locking is achieved in a 2 μm GaSb-based laser up to 60 °C. The laser has a T0 of ~82 K at room temperature, and the absorber bias voltage has little effect on T0.